Pengaruh Kelas Sosial Terhadap Perilaku Konsumen (Studi Pada Pembelian Rumah di Perum Perumnas Cabang Mojokerto Lokasi Madiun) - Ria Dwi Nugraheni (Universitas PGRI Madiun, 2018)
This research aim to know social class at PERUMNAS Branch Mojokerto Madiun location, to know consumer behavior at PERUMNAS Branch Mojokerto Madiun location, and to know influence of social class to consumer behavior at PERUM PERUMNAS Branch of Mojokerto Madiun location. Determination of samples in this study using a saturated sampling technique that is as many as 56 consumers who have bought houses of various types in PERUMNAS Branch Mojokerto Location Madiun. Data collection techniques used questionnaires, observations, interviews, and documentation. The results showed that obtained the results of simple linear regression test is Y = 17.668 + 1.256 X, the constant of 17.668. The result of t test is got the value of rhitung equal to 15.163 and ttabel equal to 1.67252. If rhitung ≥ ttable, then the calculation in accordance with the test criteria t. The result shows that rhitung (15.163) ≥ ttable (1.67252), it can be concluded that Ha accepted dah Ho rejected that social class significantly influence consumer behavior (Study on Purchase of House in PERUM PERUMNAS Branch of Mojokerto Madiun Location).